The differences of pulse on the day of training based on hours sleep - Samodra, Yohanes Touvan Juni (UIR Press, 2021)
The quality of rest will give a good result for the adaptation of the exercise. Exercise is carried out, so that physical condition has improved. The pulse rate is an indicator that can be used to see the process or results of exercise adaptation. If the waking pulse rate is still high, it can be assumed that time is still needed to rest. This study aims to determine the difference in the pulse rate of waking up from samples who sleeps more than 6 hours and 6 hours below. The research is carried out by experiment. The sample is given 75% weight training with 12 tools for 12 meetings. Pulse measurement is done independently before and upon waking. Data are analyzed using the T-test. Based on the results, it is reported that 25 people are trying to rest 6 hours down and 47 times resting above 6 hours. Based on the T-test analysis, it is found that there is a significant difference between respondents who sleep less than 6 hours and more than 6 hours with a significance of .002 with a mean of -0.8 for those who rested 6 hours and less and 4.6 for those who sleep more than 6 hours. This research can be replicated by considering several variables related to the acceleration of recovery, including Vo2Max, blood HB, and it is necessary to consider the differences between sons and daughters.